2018
DOI: 10.1371/journal.pone.0198344
|View full text |Cite
|
Sign up to set email alerts
|

Performance of point-of-care birth HIV testing in primary health care clinics: An observational cohort study

Abstract: BackgroundFailure to timely diagnose HIV in infants is a major barrier for scaling-up paediatric antiretroviral treatment (ART). WHO recommends birth testing for earlier diagnosis and to improve test coverage, but current diagnosis takes 2–3 weeks to complete, thereby limiting the ability of care givers to provide follow-on care, especially in low-resource settings. We evaluated the benefit of implementing rapid diagnosis of HIV at birth in primary health care maternity wards in Mozambique.Methods and findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 22 publications
2
25
1
Order By: Relevance
“…This indicates that with minimal extra training and support, clinical staff already employed within the hospital can successfully process POC samples using GeneX. The at birth POC error rate observed in our study (8.5%) was higher than at 6 weeks (2.6%), however comparable to that observed in other studies (4.8%-11%) [17,27,43]. Higher error rates at birth could be a result of difficulty collecting adequate sample from infants.…”
Section: Plos Onesupporting
confidence: 82%
See 1 more Smart Citation
“…This indicates that with minimal extra training and support, clinical staff already employed within the hospital can successfully process POC samples using GeneX. The at birth POC error rate observed in our study (8.5%) was higher than at 6 weeks (2.6%), however comparable to that observed in other studies (4.8%-11%) [17,27,43]. Higher error rates at birth could be a result of difficulty collecting adequate sample from infants.…”
Section: Plos Onesupporting
confidence: 82%
“…Testing infants earlier (at birth) and with a more efficient point of care (POC) HIV diagnostic technology is emerging as a strategy to streamline EID, minimize challenges with traditional central laboratory-based PCR testing, and bridge the gap between EID demand and laboratory capacity. POC diagnostic technologies such as GeneXpert HIV-1 Qual [ 15 ] and Alere m-PIMA [ 16 ] are cartridge-based tests that can be processed at the hospital by trained clinical or laboratory staff and can result in more rapid turnaround times of results, more infants being identified as HIV-positive and more infants initiated on ART at younger ages than traditional testing strategies [ 17 22 ]. Studies have shown high sensitivity and specificity of POC testing and found that POC implementation is feasible in hospital-based settings in Kenya [ 23 , 24 ], South Africa [ 18 , 25 27 ], Mozambique [ 28 ], and Tanzania [ 29 ]; is acceptable to providers [ 26 ] and patients [ 30 ]; and may be a cost-effective option for EID [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…With funding from Unitaid, the Elizabeth Glaser Pediatric AIDS Foundation (EGPAF) worked with the Ministry of Health of the Kingdom of Eswatini to pilot POC birth testing in three health facility maternity units, starting in 2016, building on an existing program of early infant testing using POC platforms. POC testing has been shown to reduce median turnaround time of results at 6 week testing from 55 to 0 days [13] and has also been shown to be feasible for testing at birth [14,15]. The opportunity to offer POC birth testing allows most caregivers to receive results before they are discharged from the hospital after delivery, or shortly thereafter, and thus can improve the survival chances of those found to be infected by starting treatment earlier.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the thirty and two additional studies with no comparative testing included reported on the clinical utility of POC results [1417]. Of the two field reviews that reported on clinical utility [15, 17], one was a field feasibility evaluation study [14] and the other a cluster-randomized trial [16]. POC results were used for clinical management in two studies [14, 15].…”
Section: Resultsmentioning
confidence: 99%